Rationale and design of a randomized, double-blind, event-driven, multicentre study comparing the efficacy and safety of oral rivaroxaban with placebo for reducing the risk of death, myocardial infarction or stroke in subjects with heart failure and significant coronary artery disease following an exacerbation of heart failure: the COMMANDER HF trial - Zannad, Faiez; Greenberg, Barry; Cleland, John G.F.; Gheorghiade, Mihai; van Veldhuisen, Dirk J.; Mehra, Mandeep R.; Anker, Stefan D.; Byra, William M.; Fu, Min; Mills, Roger M. (European journal of heart failure, 2015)
Aims Thrombin is a critical element of crosstalk between pathways contributing to worsening of established heart failure (HF). The aim of this study is to explore the efficacy and safety of rivaroxaban 2.5 mg bid compared with placebo (with standard care) after an exacerbation of HF in patients with reduced ejection fraction (HF‐rEF) and documented coronary artery disease. Methods This is an international prospective, multicentre, randomized, double‐blind, placebo‐controlled, event‐driven study of approximately 5000 patients for a targeted 984 events. Patients must have a recent symptomatic exacerbation of HF, increased plasma concentrations of natriuretic peptides (B‐type natriuretic peptide ≥200 pg/mL or N‐terminal pro–B‐type natriuretic peptide ≥800 pg/mL), with left ventricular ejection fraction ≤40% and coronary artery disease. Patients requiring anticoagulation for atrial fibrillation or other conditions will be excluded. After an index event (overnight hospitalization, emergency department or observation unit admission, or unscheduled outpatient parenteral treatment for worsening HF), patients will be randomized 1:1 to rivaroxaban or placebo (with standard of care). The primary efficacy outcome event is a composite of all‐cause mortality, myocardial infarction or stroke. The principal safety outcome events are the composite of fatal bleeding or bleeding into a critical space with potential permanent disability, bleeding events requiring hospitalization and major bleeding events according to International Society on Thrombosis and Haemostasis bleeding criteria. Conclusion COMMANDER HF is the first prospective study of a target‐specific oral antithrombotic agent in HF. It will provide important information regarding rivaroxaban use following an HF event in an HF‐rEF patient population with coronary artery disease.